Optimalisasi Peran Orang Tua dan Guru dalam Mendidik Generasi Z melalui Webinar Pengabdian Masyarakat - Elkarimah, Mia Fitriah; Tiwiyanti, Leni; Fuadah, Siti; Mubasyira, Muthia (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
An online webinar with the theme "Becoming Parents Who Are Ready to Make Friends with Gen Z" was organized by the Hayatinnur Islamic Education Foundation on December 7, 2024. This activity aims to increase parents' understanding of the characteristics and challenges faced by Generation Z in the digital era, as well as provide strategies for recognizing children's social-emotional aspects to shape national character. The webinar, which was held online via Zoom and broadcast live on YouTube, was attended by 67 participants consisting of parents, teachers, and the general public. Competent resource persons, namely Teguh Purwandono Septiyanto, S.Kom., and Muhammad Husni Mubarok, S.S., presented the material interactively, accompanied by moderator Three Yuliasih Sugiarti, S.T. The implementation of the webinar involved a committee from the SD IT Bina Insani Muslim committee and a team of lecturers from Universitas Indraprasta PGRI (Unindra). The evaluation results show that participants feel more prepared and confident in dealing with technological developments and building effective communication with Generation Z children. This activity makes a positive contribution in supporting the role of parents as the main companions in the development of children's character in the modern era.